Perfil de tolerancia ocular de un cosmético para bebe in vivo (2012)
ABSTRACT: The study that is performed for health registration before marketing any cosmetic product assures its safety and efficacy to prevent a public health problem. Objective: to describe the possible eye risk caused by a shampoo for babies through in vivo testing. Methods: a clinical exploratory and hermeneutic study based on direct macroscopic observation of clinical effects; determination of average effects in 6 rabbits by the OECD value scale and a histopathological study of a sample of eye tissue. Results: fifty percent of rabbits showed level 1 ocular injury; 16.67 % suffered level 2 whereas 33.33 % had level 3. None of the animals reached level 4 (maximum level in injuries). The analysis of the average clinical effects and the histopathological study confirmed the sensitivity of the rabbit as experimental reference that may be applicable to babies. Conclusions: the shampoo might cause mild eye effects; however the possible ocular risk must be stated until such time as the safety of the product is proven.